1990
DOI: 10.1084/jem.171.5.1665
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of the T cell repertoire. Self tolerance causes a shift of T cell receptor gene usage in response to insulin.

Abstract: Bovine insulin(BI)-specific I-Ab-restricted T cell clones have been characterized for fine specificity and TCR gene usage. We have demonstrated that mouse strains carrying H-2b on three different genetic backgrounds (C57BL, BALB, and 129) rearrange and express the V beta 6 gene in a large proportion (36%) of insulin-specific clones. In these strains, the non-MHC background did not seem to influence TCR gene usage in response to BI. The V beta 6+ clones appeared to be selected by the antigen. In contrast, no V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

1990
1990
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 44 publications
4
18
0
Order By: Relevance
“…Processing is inhibited by chloroquine or prior fixation of APC. Disruption of the disulfide bonds in insulin by performic acid oxidation or reduction and alkylation destroys its capacity to stimulate cloned and polyclonal T cells (8,12,13,17). This can be interpreted to indicate that an intact A chain loop structure or disulfide-linked B chain residues are essential components of the major determinant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Processing is inhibited by chloroquine or prior fixation of APC. Disruption of the disulfide bonds in insulin by performic acid oxidation or reduction and alkylation destroys its capacity to stimulate cloned and polyclonal T cells (8,12,13,17). This can be interpreted to indicate that an intact A chain loop structure or disulfide-linked B chain residues are essential components of the major determinant.…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that the T cells recognized a confor-mational determinant containing essential residues from both the A and B chains of insulin. Others have described experiments in which mouse and human A chain loop-reactive T cells were stimulated by A chain peptides with no associated B chain residues (9)(10)(11)(12)(13). These results indicate that at least some loop-reactive T cells recognize determinants within the A chain.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…M. Seman Laboratoire d'Immunodiff6renciation, Hall de Biotechnologies, Universit6 Denis Diderot (Paris 7), BP 7124, 2 place Jussieu, F-75251 Paris Cedex 05, France see Tomonari et al 1993). Tcr diversity resulting from VJ or VDJ recombinations and N sequences generates alternative repertoires to conventional Ags that might prevent deletion of Tcrb-V-expressing T cells induced by Sags to profoundly alter the immunological responder status (Davis and Bjorkman 1988;Frangoulis et al 1989;Falcioni et al 1990). Yet, a controversy exists as to whether T-cell clone anergy or deletion induced by Sags might contribute to the immunodeficiency observed in mice infected by the mouse leukemia virus or in HIV-infected patients (Htigin et al 1991;Imberti et al 1991;Kanagawa et al 1992;Laurence et al 1992).…”
Section: Introductionmentioning
confidence: 99%